Phencyclidine interactions with the ionic channel of the acetylcholine receptor and electrogenic membrane - Albuquerque, Edson X. (1980)
The effects of phencyclidine (PCP) were studied on the electrogenic and chemosensitive properties of the neuromuscular junction of skeletal muscle as well as on the binding sites on the acetylcholine (AcCho) receptor and its ionic channel in the electric organ membranes of the electric ray. The directly elicited muscle twitch was markedly potentiated by prolonging the falling phase of the muscle action potential and blocking delayed rectification. The indirectly elicited muscle twitch was transiently potentiated and then blocked by PCP at concentrations below 60 μM. PCP blocked miniature endplate potentials and AcCho sensitivities at the junctional region of innervated muscle, blocked the extrajunctional sensitivity of the chronically denervated muscle, and significantly depressed the peak amplitude of the endplate current (EPC) in a voltage- and time-dependent manner. PCP also caused acceleration of the time course of EPC decay and shortening of the mean life-time of the open ionic channel. The effects of PCP were not due to inhibition of AcCho receptor sites because PCP did not protect against the quasi-irreversible inhibition of receptor sites by α-bungarotoxin, nor did it inhibit binding of [(3)H]AcCho or [(125)I-labeled α-bungarotoxin to the receptor sites. On the other hand, PCP blocked the binding of [(3)H]perhydrohistrionicotoxin to the sites of the ionic channel of the AcCho receptor. The data suggest that PCP reacts with the electrogenic K(+) channel and the ionic channel associated with the AcCho receptor in the open as well as the closed conformation.